KAUSALITAS KAIDAH HETERONOM PEMBENTUKAN OMNIBUS LAW KLASTER KETENAGAKERJAAN DALAM PERSPEKTIF POLITIK HUKUM DI INDONESIA - Sarira, Iron (Faculty of Law, Universitas Tanjungpura, 2024)
AbstractOmnibus Law is a product of positive law compilation in Indonesia that requires political and economic interests related to its procurement. Especially in the fourth cluster on Manpower has started planning since mid-2019 to revise Law Number 13 of 2003 concerning Manpower is considered to be ineffective. Thus, a new regulation is needed that is capable of improving the investment climate to attract foreign investors (investment) to establish their businesses in Indonesia. Job Creation Law has been enacted, and specifically for the Employment Cluster which has the four implementation rules are in the form of Government Regulations, However, This legal vacuum prompted the government to create Government Regulation in Lieu of Law (Perppu) Number 2 of 2022 on December 30, 2022, because there is a